Inokulasi Fungi Mikoriza Arbuskular dan Pemupukan Fosfor pada Padi Gogo (Oryza sativa L.) - Hifnalisa Hifnalisa (Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Inoculation of Mycorrhiza Arbuscular Fungi and Fertilization of Phosphorus on Dry Land Rice (Oryza sativa L.)ABSTRACT. The experiment was conducted in Banda Aceh since May to July 2007. The objective of study were to study the effect of mycorrhiza arbuscular fungi and phosphorus fertilization dosage on yield of dry land rice. The study was arranged in factorial randomized completely block design with two factorial. The first factor is inoculation of mycorrhiza arbuscular, fungi, namely: without inoculation (Io), inoculation with Entrophospora sp. (I1), and Inoculation with Acaulospora sp. (I2). The second factor is fertilization of phosphorus, namely: 0 g.pot-1 (Po), 3,75 g.pot-1 (P1), 7,50 g.pot-1 (P2), 11,25 g.pot-1 (P3). The result showed that inoculation of mycorrhiza arbuscular fungi increased fresh and dry weight of root, fresh and dry weight of shoot, number of tiller, 100 seed weight, number of tassel. The best treatment was found on inoculation of Entrospora sp. and fertilization of 11,25 g.pot-1.